Gender, Migration and the Intergenerational Transfer of Human Wellbeing - Wright, Katie (Springer International Publishing, 2018)
This book discusses how human wellbeing is constructed and transferred intergenerationally in the context of international migration. Research on intergenerational transmission (IGT) has tended to focus on material asset transfers prompting calls to balance material asset analysis with that of psychosocial assets - including norms, values attitudes and behaviors. Drawing on empirical research undertaken with Latin American migrants in London, Katie Wright sets out to redress the balance by examining how far psychosocial transfers may be used as a buffer to mediate the material deprivations that migrants face via adoption of a gender, life course and human wellbeing perspective. Katie Wright is Reader in International Development at the University of East London, UK. Her research focuses on gender, human wellbeing, international migration, microfinance, sustainable livelihoods and Latin America. Her previous monograph, International Migration, Development, Human Wellbeing and International Migration (2012) drew on Economic and Social Research Council funded work in this area. .